The comparison of decision-making in ambiguous situations and galvanic skin responses as somatic markers in patients with posterior cortex epilepsy and mesial temporal lobe epilepsy with hippocampal sclerosis. Issue 10 (26th November 2022) - Şandor, Serra; Yağcı Kurdish, Selin; Delil, Şakir; Türk, Bengi Gül; Yeni, Seher Naz
ABSTRACT: Introduction: Decision-making behaviors of patients with mesial temporal lobe epilepsy (MTLE) is a subject that has been studied frequently. However, determining the neuropsychological profiles of patients with different types of epilepsy is also important. Our main purpose was to examine the decision-making behaviors of patients with posterior cortex epilepsy (PCE) through the assumptions of somatic marker hypothesis (SMH) and to compare their performances with those of a MTLE group and a control group. Method: Participants comprised of 13 patients with PCE (mean age 30.92 ± 9.99 years); 14 patients with MTLE with hippocampal sclerosis (MTLE-HS) (mean age 25.53 ± 7.40 years) and 15 controls (mean age 24.60 ± 8.45 years). Decision-making performances were assessed with the Iowa gambling test (IGT) and anticipatory skin responses before each choice were recorded. A comprehensive neuropsychological test battery was also given to all participants in order to examine the relationship of decision-making with other cognitive functions. Results: Anticipatory responses before choosing from disadvantageous decks were significantly larger than choosing from advantageous decks in the PCE group ( p = 0.00). No significant difference was found between the PCE and control group's total net scores. IGT total net scores was significantly correlated with Stroop test interference time ( p = 0.03). Conclusion: The study reveals that cognitive impairments of patients with PCE are not limited to brain's posterior areas' functions, and provides evidence for the current paradigm which understands epilepsy as a network disorder.